Analysis Of Factors Influencing The Volume Of Cocoa Bean Exports In Indonesia - Bq. Nining Riskya Ramdhani; Ni Putu Martini Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Cocoa is one of the plantation commodities that plays an important role in economic activities in Indonesia. Cocoa commodities have export market opportunities, so they can increase foreign exchange. This study aims to analyze the amount of production, international prices and land area that affect the volume of cocoa bean exports in Indonesia. The data used in this study are time series data from 1990 to 2022. The data analysis techniques used in the study are multiple linear regression analysis, classical assumption test, F test and T test. The results of the study found that simultaneously the variables of production, international prices, and land area have a significant effect on the volume of cocoa bean exports in Indonesia. Partially, the variables of production and international prices have a positive and significant effect on the volume of cocoa bean exports in Indonesia, while the partial variable of land area has a negative effect on the volume of cocoa bean exports in Indonesia. The results of this study can provide a basis for designing policies and strategies that support increasing the volume of cocoa exports in Indonesia for stakeholders, including the government, farmers, and exporters. The government needs to formulate policies that support increasing the area of ​​land and productivity of cocoa.